Mewujudkan Keberlanjutan Ekonomi Lokal Sektor UMKM melalui Strategi Collaborative Governance di Kabupaten Ngawi - Anwar, Khoyrul; Wijayanti Mala, Istiana; Misnan, Misnan (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
The study aims to analyze the implementation of collaborative governance in realizing the sustainability of the local MSME sector economy. The study used a descriptive qualitative method. Interview, observation, and documentation techniques were used to collect data. Data analysis is conducted interactively and continues until completion. To ensure data credibility, researchers used source triangulation techniques. The results of the study show that the implementation of collaborative governance has demonstrated its strategic role in supporting local economic sustainability. The collaboration that has been established reflects the existence of cross-actor synergies that are relatively effective, both vertically and horizontally, as well as in terms of partnership relations. With the local government as the main facilitator, the Ngawi MSME Association has strengthened coordination and empowerment at the grassroots level. Effective coordination, utilization of digital technology, and active involvement of MSME players are three interrelated key elements in determining the success of such collaboration. Cross-level and cross-sector coordination can improve the effectiveness of program implementation, technology utilization, expand market access, and increase the competitiveness of MSMEs.